Konsep Pendidikan Adab dalam Kitab Al-Jí¢mi' Al-á¹¢aá¸¥í®á¸¥ Karya Imam Al-TirmiÅ¼í® dan Relevansinya dengan Tujuan Pendidikan Nasional - Haryanto, Haryanto (Tawazun: Jurnal Pendidikan Islam, 2021)
The character education program launched by the Government has not reaped encouraging results, as evidenced by the worsening moral decline that occurs in the midst of the nation's children, such as corruption, drug abuse, LGBT lifestyle, free sex association, fighting between students, students and villagers, intolerance among religious people, separatism that threatens the integrity of the Republic of Indonesia, and so forth. The concept of education in imam al-TirmiÅ¼í®'s al-Jí¢mi' al-á¹¢aá¸¥í®á¸¥ explains in detail the basic potential of man (heart, reason, taste, initiative and body), and explains the relationship between an individual and religious principles, with oneself and with his environment. The concept is very relevant to the purpose of national education, which is noble and morally praiseworthy to be able to improve the quality of individuals, families and communities to build a just and civilized national and state order, to further achieve the ideals of social justice for all Indonesians. Abstrak Program pendidikan karakter yang dicanangkan oleh Pemerintah belum menuai hasil yang menggembirakan, dibuktikan dengan semakin parahnya kemunduran moral yang terjadi di tengah-tengah anak bangsa, seperti korupsi, penyalahgunaan obat-obat terlarang, gaya hidup LGBT, pergaulan seks bebas, tawuran antar pelajar, mahasiswa dan warga kampung, intoleransi antar umat beragama, separatisme yang mengancam keutuhan NKRI, dan lain sebagainya. Konsep pendidikan adab dalam kitab al-Jí¢mi' al-á¹¢aá¸¥í®á¸¥ karya Imam al-TirmiÅ¼í® menerangkan secara terperinci dalam mengembangkan potensi dasar manusia (hati, akal, rasa, karsa dan raga), serta menjelaskan relasi antara seorang individu dengan prinsip-prinsip agama, dengan diri sendiri dan dengan lingkungannya. Konsep sangat relevan dengan tujuan pendidikan nasional, yangmana adab mulia dan akhlak terpuji mampu meningkatkan kualitas individu, keluarga dan masyarakat untuk membangun tatanan berbangsa dan bernegara yang berkeadilan dan beradab, untuk selanjutnya mencapai cita-cita keadilan sosial bagi seluruh rakyat Indonesia.